A 1.8 V 8.62 µW Inverter-based Gain-boosted OTA with 109.3 dB dc Gain for SC Circuits. Issue 6 (2nd November 2019) - Kaliyath, Yajunath; Laxminidhi, Tonse
ABSTRACT: This paper presents a low-power inverter-based gain-boosted operational transconductance amplifier (OTA) for switched capacitor (SC) circuits operating at higher supply voltage (>1 V). The proposed OTA is implemented using UMC 180 nm CMOS technology with a supply voltage of 1.8 V and it offers a high dc gain with a unity gain bandwidth (UGB) suitable for audio applications. All the transistors of the proposed OTA are operated in sub-threshold region to minimize the power consumption. Gain-boosting technique is employed to achieve a higher dc gain. The post-layout simulations demonstrate the robust performance of the proposed OTA, which delivers a high dc gain of 109.3 dB and a UGB of 5.29 MHz at 81° phase margin (PM) with a capacitive load of 2.5 pF for a typical process corner at room temperature (27°C). The proposed OTA draws a quiescent current ( I Q ) of 4.79 µA, resulting in a power consumption of 8.62 µW.